Argentinean agid test for diagnosis of equine infectious anemia: six years of history - Bok, Marina (2016)
Equine infectious anemia (EIA) is a disease of high economic impact on the equine industry worldwide. Since horses are frequent travelers, EIA falls under strict regulatory control programs in many countries. In Argentina the national animal health authority (SENASA) states that all horses imported, moving within the country, or congregating at public assemblies must have a negative EIA report conducted within the previous 2 months. The agent causing EIA is a RNA virus from the Retroviridae family and its major capsid protein named p26 is the most immunogenic protein in the viral particle. Thus, the detection of specific antibodies directed to p26 is the aim of most diagnosis tests available in the world. The agar gel immunodifusion (AGID) is the officially accepted method to certify the diagnosis of EIA in Argentina. Since 2009 IncuINTA was working on the scaling up and production of the KIT AIE IDGA RP26, an Argentinean AGID test entirely developed in the laboratory containing a recombinant p26 protein to detect EIA antibodies in horses’ serum. Until 2015 IncuINTA produced two pilot batches and six commercial batches (one per year) containing from 24000 determinations in 2011 to 39600 determinations in 2015. Since the product was launched in 2011, the sales were increased 109%. Up to date we have placed on the market 170640 determinations. As expected, the number of laboratories buying the KIT AIE IDGA RP26 was also increasing through time being 26 in 2011 and 36 in 2015. This number of clients represents 17% of the 207 laboratories authorized by SENASA to diagnose EIA in Argentina. These laboratories are located mostly in Buenos Aires, Santa Fe, Entre Ríos, Formosa, La Pampa, Rio Negro, Cordoba, Corrientes, Salta and Tucum an provinces. Until 2009 there was no Argentinean EIA test available in our market being the imported ones very expensive. IncuINTA, which is a R&D laboratory, could scale up, produce and sell the KIT AIE IDGA RP26 during six consecutive years. After this success, IncuINTA perspective is to increase the number of batches each year to be able to attend the demand of most diagnosis laboratories in the country.